2000
DOI: 10.1159/000010210
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Value of Selective Salpingography for Infertile Women with Patent Fallopian Tubes: The Impact on Pregnancy Rate

Abstract: Objective: To determine the therapeutic value of selective salpingography (SSG) for infertile women with patent fallopian tubes. Design: Retrospective, case-control analysis. Setting: University Hospital, infertility clinic. Patients: Infertile cases with patent tubes documented by hysterosalpingography (HSG) or by HSG followed by laparoscopic examination (n = 80). Intervention(s): Hysteroscopic SSG. Main Outcome Measure(s): Patency rate of tubes by SSG. Pregnancy rate following SSG. Result(s): Eighty cases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…One small, retrospective, case-control study reported a high spontaneous conception rate after selective salpingography in infertile women with patent fallopian tubes. 44 Tubal perfusion pressures were not assessed in this study. It would be reasonable to speculate that the procedure may have treated a currently unrecognised pathology, by reduction of tubal perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…One small, retrospective, case-control study reported a high spontaneous conception rate after selective salpingography in infertile women with patent fallopian tubes. 44 Tubal perfusion pressures were not assessed in this study. It would be reasonable to speculate that the procedure may have treated a currently unrecognised pathology, by reduction of tubal perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper emphasized the value of selective salpingography, as an adjunct to HSG in infertile patients, even if it the tubes were shown to be patent, as pregnancy rates were significantly higher in the selective salpingography group [28]. This is in favor of the ªtubal plug or tubal debrisº theory.…”
Section: Discussionmentioning
confidence: 99%